New water mites species (Acariformes: Hydrachnidia) from the Far East of Russia - Tuzovskij, Petr V.; Semenchenko, Ksenia A. (Zootaxa, 2009)
Illustrated descriptions of five water mite species, Sperchon (Hispidosperchon) nevelskoii sp. n., Teutonia (Subteutonia) minor sp. n., Lebertia (Mixolebertia) sokolowi sp. n., Mixobates amurensis sp. n. and Feltria (Feltria) orientalis sp. n., from running and standing waters of the Far East of Russia are presented.